Dampak Perubahan Hutan Menjadi Kebun Kakao Terhadap Keanekaragaman Laba-Laba (Araneae) di Sulawesi Tengah - Shahabuddin Shahabuddin; Abd. Wahid Abd. Wahid; Elijonnahdi Elijonnahdi (Biology Department, Mathematics and natural science, Tadulako University, 2011)
This study aims to evaluate the effect of forest conversion to agriculture, especially cocoa plantation on spider diversity in Central Sulawesi. The experiment was conducted in the vicinity of the village of Bobo Palolo Subdistrict, Donggala in the margins of Lore Lindu National Park in Central Sulawesi. Spiders were collected on transects size of 50 mx 10 m at each study site using insect nets. The results showed that there are at least 17 species from 11 families of spiders recorded from natural forest, disturb forest, and cacao plantation. Changes in habitat type affect the diversity of spiders. Spider species diversity tends to decline due to habitat change from natural forest to cocoa plantations. However the forest with intermediate level of disturbance as well as a cacao plantation that maintains many types of shade trees has capability for supporting spiders diversity. Community structure of spiders at the cacao plantation are relatively similar to those in natural forests.